Financial Engineering - Sugeng Widodo (At-Tauzi : Jurnal Ekonomi Islam, 2009)
The financial market and technology have experienced rapid and unpredictable changes which have an impact on the increasing demand for Islamic financial products. At the same time, Islamic financial institutions face competition from conventional financial institutions, among others due to mergers, collaborations, the discovery of new financial products and services. In order to answer that challenge, it is necessary to develop/engineer Islamic financial products while prioritizing the fulfillment of its sharia aspects as well as meeting market considerations that can be done using the concept of: imitation, mutation of traditional Islamic financial products and innovation